Development and evaluation of an automatic software for management zone delineation - Albornoz, Enrique Marcelo; Kemerer, Alejandra Cecilia; Galarza, Romina; Mastaglia, Nicolás; Melchiori, Ricardo Jose; Martínez, César Ernesto (2018)
The lack of availability of user-friendly and automatic software for management zone delineation is limiting the adoption of site-specific management practices. Several procedures for management zone delineation have been proposed, but they commonly require the use of different software, or advanced GIS and statistical skills of users, which limit their adoption. This study proposes a user-friendly and automatic software that would integrate all steps in order to delineate management zones and make prescription files. The software includes importation of different input data layers, re-projection and resizing data in a common grid size. An integrative index was proposed for the selection of the optimal number of zones after clustering analysis. Users are guided by graphical windows showing intermediate results. Also, additional automatic post-processing techniques to improve size, shape and fragmentation of delineated zones are available. The final step allows generation of the ESRI Shapefile required to make variable rate prescriptions by zone with minimal user intervention. The performance of the approach was evaluated for management zone delineation using single and multiple layers of data by comparing with Management Zone Analyst software, and the improvement of the approach in the selection of the optimal number of zones and reducing zone-fragmentation was shown. The software design includes a simple graphical user interface and requires minimal user intervention in order to assist the end-user. The main contribution of this work was the successful development of this automatic user-friendly solution that includes all the necessary steps for management zone delineation and prescription file generation.